Penerapan Teknologi Robotic Ship Fishery untuk Pemberdayaan Nelayan Desa Surodadi Kabupaten Demak - Supari Supari; Aria Hendrawan; Purwanto Purwanto (Jurnal Surya Masyarakat, 2026)
Traditional fishermen in Surodadi Village face productivity constraints due to their reliance on conventional fishing gear and the lack of post-harvest facilities. This community service program offers a solution through the planned implementation of Internet of Things (IoT)-based Robotic Ship Fishery (RSF) technology and the construction of cold storage infrastructure. The implementation method uses the Participatory Rural Appraisal (PRA) approach, encompassing socialization, technical and managerial training, and hardware engineering, and involves 20 fishermen as target partners. The results indicate that the RSF prototypes are currently undergoing functional laboratory testing, while the construction of the 100 kg capacity cold storage is in the physical development phase. This intervention has significantly improved human resource cognitive capacity, with posttest evaluations showing that 100% of partners (20 people) understand the function of navigation technology for fuel efficiency and 93.3% (19 people) understand cold chain management. It is concluded that the program has successfully established a foundation for human resource readiness and a paradigm shift toward modern, independent fishery businesses. However, the real economic impacts will require monitoring following full implementation of the technology.